2007
DOI: 10.4018/jcit.2007070103
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology Adoption and the Role of Organizational Readiness

Abstract: This case describes the evolution of the use of information technology (IT) at National Banking Services, one of the oldest banks in India. It describes the bank’s response to economic liberalization and the resulting initiatives for IT adoption. It highlights the influence of organizational readiness on IT adoption. In particular, it describes the negative influence on IT adoption of conditions such as the lack of top management support, skeptical end-user attitudes about the benefits of IT, and resistance fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…In respect of the explanatory factor of organisational size, this mirrors the disagreements in the literature (Doolin and Troshani, 2007;Efendi et al, 2009;Janvrin et al, 2008). In respect of top management support and/or organisational champion, our findings are different from Tarafdar and Vaidya (2007) and Neufeld et al (2007) which noted their catalyst role. Further, the study suggests that organisational factors in themselves will not influence XBRL adoption.…”
Section: Par 231contrasting
confidence: 71%
See 1 more Smart Citation
“…In respect of the explanatory factor of organisational size, this mirrors the disagreements in the literature (Doolin and Troshani, 2007;Efendi et al, 2009;Janvrin et al, 2008). In respect of top management support and/or organisational champion, our findings are different from Tarafdar and Vaidya (2007) and Neufeld et al (2007) which noted their catalyst role. Further, the study suggests that organisational factors in themselves will not influence XBRL adoption.…”
Section: Par 231contrasting
confidence: 71%
“…DePietro et al (1990) describe the organisational context factors (Figure 1) as those which constitute an organisation's readiness to adopt technology. The decision to adopt a technology such as XBRL may be influenced by the top management of the organisation, as suggested by Tarafdar and Vaidya (2007), who studied the adoption of technology in an Indian bank. As top management has authority and control over organisational resources, failure to gain support from top management can result in a failed technology adoption (Troshani and Doolin, 2005).…”
Section: Environmental Contextmentioning
confidence: 99%
“…In reviewing IT academic literature, one finds that a wide range of firm‐level factors have the potential to enable IT adoption, including those relating to a firm's technological opportunism, technological orientation, organizational innovativeness, technology portfolio and absorptive capacity (Tsikriktsis et al , 2004), or factors related to top management support, organization culture, and characteristics of IS professionals (Tarafdar and Vaidya, 2007). As for e‐learning adoption specifically, the organizational factors highlighted refer either to firm's characteristics such as size, sector, industrial relations system (unions) and single or multi‐location establishment (Nisar, 2002), or to employees' characteristics such as level of education, rank of position, gender, competencies (computer and internet self‐efficacy, cognitive absorption) (Cheng, 2011; Nisar, 2002).…”
Section: E‐learning Adoption and Assimilation Factorsmentioning
confidence: 99%
“…By comparing the company voluntarily submit the XBRL data, Ronald (2008) found that the company size, liquidity and profitability significantly affect the XBRL standards adoption and diffusion. Through studying the XBRL application example on the South Africa and other countries, Carolyn (2012) found that government policies, corporate initiative and non-uniform standard is the main factors influencing the XBRL promotion [12] . Pan Yan (2006) had studied in XBRL ledger design aim, operation mechanism, the development process and the financial report mode optimization, etc.…”
Section: The Research On the Xbrl Taxonomy Standards Development And mentioning
confidence: 99%